2003
DOI: 10.1177/00343552030460030101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Characteristics of Work Environments and Employers Open to Hiring and Accommodating People with Disabilities

Abstract: This study determined the characteristics of employers who are open to hiring and supporting people with disabilities. The purpose was to help rehabilitation professionals better target their placement and educational activities. Using a grounded theory qualitative approach, the researchers conducted focus groups and interviews with employers, employed persons with disabilities, and experienced rehabilitation placement professionals. The results indicated that 13 specific characteristics, organized into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 6 publications
12
127
0
2
Order By: Relevance
“…The opportunity of subsidized labor in combination with high employer taxes, as reflected in the Swedish culture of free labor that forms part of the traditional and obligatory rehabilitation route, may have influenced employer readiness to open the door. The group of socially committed employers in the present study can reasonably be assumed to be transferable to other national contexts since similar findings are found in other countries (Gilbride et al, 2003;Ju et al, 2013).…”
Section: Methodological Considerationssupporting
confidence: 87%
See 3 more Smart Citations
“…The opportunity of subsidized labor in combination with high employer taxes, as reflected in the Swedish culture of free labor that forms part of the traditional and obligatory rehabilitation route, may have influenced employer readiness to open the door. The group of socially committed employers in the present study can reasonably be assumed to be transferable to other national contexts since similar findings are found in other countries (Gilbride et al, 2003;Ju et al, 2013).…”
Section: Methodological Considerationssupporting
confidence: 87%
“…In one study (Gilbride et al, 2003), several employer characteristics were similar to those found in our study, including view of the vocational service as an asset and support, tolerance of diversity, positive ethos, adapting a personal approach, and striving to make an appropriate job-person match. Hence, there are common features among those employers who will hire various disability groups and those who invite persons with SMI into their workplace.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Social inclusion in the labour market is perceived as an important component of participation; simultaneously, many people, including people with disabilities and reduced work capacity, do not have access to the labour market (Statistics Sweden 2016). Attention has focused on the subject of social inclusion as a meaningful factor in ensuring employment (Gilbride et al 2003) However, relatively few studies examine social inclusion more broadly, examining the qualitative aspects of working conditions for people with disabilities (Schur et al 2009). In order to open up the labour market for people with disabilities it is of interest to understand how people with disabilities are establishing themselves in the labour market and how social inclusion is experienced by these workers as well as how their working conditions influence their experiences with social inclusion.…”
Section: Introductionmentioning
confidence: 99%